Universality of good conscience and morality: an expository study with special reference to Islamic paradigm - Ansari, Abdul Haseeb (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Morals are just, fair and good rules of human relations and human behaviours. Good conscience also comprises certain principles for imparting justice and fairness among the people. God conscience and morality are, thus, close to each other. Universality in good conscience will certainly help in developing universal moral rules. But the problem is: what is immoral today may be moral tomorrow; likewise, what is moral at one place may be immoral at another place. Because of this, universality in morality is not achievable. However, in Islamic morality, universality is a possibility because most of the moral rules are derived from the Qur’an and Sunnah; and man-made moral rules or rules developed as customs have to be in conformity with them. As every society has its religious and cultural identity in terms of rules governing human relations and human behaviours, it is, thus, not possible to impose cultural rules of one society on the members of other societies. However, there are a number of intercultural impacts on the people.